Faktor – faktor yang mempengaruhi indeks pembangunan manusia di Provinsi Papua Tahun 2015-2019 - Mandu Chaironi; Jalu Aji Prakoso (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2022)
This research makes use of secondary facts with panel data evaluation, consisting of time series records for 2015-2019 and go section facts for 27 towns/districts in Papua Province. The secondary statistics taken encompass the Human improvement Index (HDI), Gross regional domestic Product (GRDP), income distribution, and poverty levels. The consequences of this have a look at indicate that there's a positive have an impact on among profits distribution at the Human development Index (HDI), poverty level which has a significant poor impact at the Human improvement Index (HDI), and profits distribution which has a high quality impact on the Human development Index (IPM) in Papua Province. 2015-2019 years.